Decree-Law Of The President Of The Republic No. 101 Of The Year 2012 On Amending Some Provisions Of The Income Tax Law Issued As Per Law No. 91 Of The Year 2005 And The Determination Of Some Tax Facilities, Contribution To The Achievement Of Social Justice And Limiting Tax Evasion Incidents = قرار رئيس جمهورية مصر العربية بالقانون رقم 101 لسنة 2012 بتعديل بعض أحكام قانون الضريبة على الدخل الصادر بالقانون رقم 91 لسنة 2005 وتقرير بعض التيسيرات الضريبية والمساهمة فى تحقيق العدالة الاجتماعية والحد من حالات التهرب الضريبى - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.